Dietary Supplementation of Tannin-Extracts to Lambs: Effects on Meat Fatty Acids Composition and Stability and on Microbial Characteristics - Biondi, Luisa (Foods, 2019)
Two extracts derived from plant material rich in hydrolysable (Tara, T; Caesalpinia spinosa) or condensed (Mimosa, M; Acacia mearnsii) tannins were added to lamb’s diet and their effects on meat quality and on microbial population were evaluated; a diet without tannins represented the Control (C). Meat pH, vitamin E, intramuscular fat content and muscle fatty acid composition were determined. Oxidative stability and microbiological analyses were performed on meat samples after 0, 4 and 7 days of refrigerated storage. Psychrotrophic bacteria were identified through MALDI-TOF MS analysis. Regarding meat fatty acids, Tara treatment decreased the percentage of monounsaturated fatty acids. The counts of all microbial groups were similar among dietary treatments at day 0, while a significant reduction of microbial loads was observed in T-group at day 7. Pseudomonas fluorescens group count was significantly affected by T extract supplementation. The MALDI-TOF MS identification revealed the dominance of Pseudomonas fragi species in all samples while Pseudomonas lundensis, Brochothrix thermosphacta and Candida famata were revealed only in control ones. In conclusions, the tannin extract supplementation is a promising dietary strategy to preserve lamb meat quality.